The importance of companionship and its impact on the call to God in the three religions - Nazmia Karim Juma Al-Azzawi (Genius Journals, 2022)
Praise be to God for the beautiful blessings. Praise be to God who has honored the privileged of His servants with intimacy in religion, and enabled them to honor His faithful servants, and adorned themby qualitiesThe honorable and the kindly gentle, politely with the best of mankind, and the master of the nation, Muhammad bin Abdullah bin Abdul Muttalib, may God’s prayers and peace be upon him. The etiquette of companionship and good manners has its faces, and I will show some of them that indicate the morals of the believers and the etiquette of the righteous,So if the souls unite and agree, relationships are strengthened, and companionship is a noble word, bearing the highest meanings and the deepest connotations. What if that relationship won the honor of being associated with the best saying, and the greatest will?!. What if he achieved that title (companion)?. AndGood companionship is also the way to success. Because the righteous encourage those who accompany them to do good, and guide them on the path of progress and success; for they regard each one of men as their relative, dear to them, as their lover; They advise him and advise him of what will benefit him in his religious and worldly affairs, and he will be assured of goodness and happiness in the immediate and the future. As for the bad, corrupt people, on the contrary, they are envious and hate everyone in human society. . company One of the main influences in human life; Because it constitutes a major factor in the formation of the personality, and its formulation in the form of good or bad, and young people in the stages of physical upbringing and mental formation learn from companionship what they do not learn from home and school; Because man is tempted to imitate the companions and friends who accompany him, especially peers and relatives, who share behavior and hobbies that permeate their guts in the paths of youth, the paths of childhood, and the paths of innocent life.
Keywords: companionship; dawah; success; morals